Dosimetric analysis of Tomotherapy-based intracranial stereotactic radiosurgery of brain metastasis. (August 2018) - Agostinelli, S.; Garelli, S.; Gusinu, M.; Zeverino, M.; Cavagnetto, F.; Pupillo, F.; Bellini, A.; Taccini, G.
Highlights: HTSRS plans achieve excellent dose conformity and homogeneity scores. Slightly flatter (1–2 mm) dose gradient compared to non-coplanar techniques. Easy treatment of multiple inplane lesions with minor degradation of the dose falloff. Care should be given when treating lesion volumes >3 cc to contain brain's V12. Analysis of interruptions suggests to split the irradiation in two sub-fractions. Abstract: Purpose: This paper analyzes Tomotherapy-based intracranial stereotactic radiosurgery (HTSRS) of brain metastasis targeting two end-points: 1) evaluation of dose homogeneity, conformity and gradient scores for single and multiple lesions and 2) assay of dosimetric criticality of completion of HTSRS procedures. Methods: 42 treatment plans of 33 patients (53 brain lesions) treated with HTSRS were analyzed. Dose to healthy brain, homogeneity, conformity and gradient indexes were evaluated for each lesion. Influence of Field Length and multiple lesions cross-talk effect were assessed. Treatment interruption and completion was investigated using radiochromic films in order to examine the delivered dose and its robustness to patient intrafraction movement. Results: The average dose homogeneity index was 1.04 ± 0.02 (SD). Average dose conformity and gradient score indexes were 1.4 ± 0.2 and 50 ± 14 respectively. We found a strong correlation of the dose to healthy brain and conformity and gradient indexes with target(s) volume for which analytical functions were obtained. Field Length and cross-talk effect were significantly correlated with poor gradient scores, but were found not to affect dose conformity. Conclusions: Homogeneity and conformity of HTSRS plans achieved excellent scores, while dose falloff and dose to healthy brain were slightly larger when compared with non-coplanar SRS techniques. Care should be given if treating large (>3 cc) or multiple near in-plane lesions in order to reduce dose to healthy brain. Analysis of interrupted treatments suggests splitting HTSRS treatments in two consecutive fractions in order to prevent target miss and overdosage due to patient intrafraction movement.